THE ROLE OF INTERNET TECHNOLOGY IN SUPPORTING E- EDUCATIONAL SERVICES MARKETING - Saleh Miralem, Maram (Acta Scientiae et Intellectus, 2024)
This paper aims to spot, examine and analyze the role of the net that it plays within the field of selling e-learning services, and it’s thought-about the most goal moreover as sub-goals, that are to spot the newest trendy developments of the net within the field of e-learning selling and also the use of electronic applications and portals to boost its potency and develop education. In addition to knowing the difficulties that hinders the role of the net to hold out its tasks in selling of e-learning in governmental and personal academic establishments. In order to attain the objectives of the paper, the scientist used the survey study approach to deal with the matter. Therefore, strengths and weaknesses are highlighted in a very variety of previous Arab and foreign studies in order that this study will like. The study processed the importance of the role that net technology plays within the field of selling e-learning services. Among the foremost necessary findings of the study is that the necessity of spreading electronic awareness, and make virtual categories through the net and quarterly tests to activate the employment of electronic portals, and also the would like for academic establishments tries to extend the effectiveness of their advertisements via the net as a primary step to achieving varied selling goals. Also, the requirement to open house for youth energies for the needs of e-learning of all age teams moreover because the proposal to conduct additional studies on the net and counsel trendy ways of developing programs and applications.